Gambaran Pelaksanaan Penyimpanan Cara Distribusi Obat Yang Baik Dan Benar (CDOB) Di PBF BUMN Dan Non BUMN Kota Batam - Aprilya Sri Rachmayanti; Mawarni Badar; Chintia Wulandari; Suci Fitriani Sammulia; Reny Haryani; Nahrul Hasan (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Good Distribution Method (CDOB) is a method of distributing or dispensing drugs and/or medicinal substances that aims to ensure quality by quality requirements and intended use in a distribution channel. Actions related to drug distribution are the acquisition, storage, and distribution of drugs from manufacturers to consumers. The use of CDOB is expected to maintain the quality of drugs received by patients and ensure conformity with the quality of drugs from the pharmaceutical industry. The research aims to find out the results of the implementation of Good Medicine Distribution Methods at PBF Enseval Putera Megatrading Tbk and PBF Kimia Farma Trading Distribution. This research is a type of observational research (evaluative non-experimental) that is descriptive in nature to get a realistic and objective picture of a condition that is currently occurring in a community group which contains questions addressed to Pharmaceutical Personnel on duty at PBF Kimia Farma and PBF Enseval Putera Megatrading Tbk Batam City. The results of research on PBF Enseval Putera Megatrading Tbk, and PBF Kimia Farma Trading Distribution, namely the score obtained from the evaluation results of CDOB implementation at PBF Enseval Putera Megatrading Tbk is in the very good category, namely with a percentage of (99%) and the score obtained from the evaluation results of CDOB implementation in PBF Kimia Farma Trading Distribution is in the very good category, namely with a percentage of (99%). Based on the research results, the description of CDOB implementation at PBF Enseval Putera Megatrading Tbk and Kimia Farma Trading Distribution is in the very good category (99%).